What causes the great green tide disaster in the South Yellow Sea of China in 2021?. (July 2022) - Zheng, Longxiao; Wu, Mengquan; Cui, Yating; Tian, Li; Yang, Pengsen; Zhao, Lianjie; Xue, Mingyue; Liu, Jiayan
Highlights: The great green tide in 2021 is extracted by NDVI and GEE. 2021 green tide reaches largest scale in history. Early recycling of P. yezoensis rafts provided more floating seed for green tide. SST was higher in June and July in the SYS, which was favorable for green tide. The lower PAR in August is conducive to reduce the effect of photoinhibition. Abstract: The largest green tide in the South Yellow Sea (SYS) of China broke out in 2021 since the first outbreak in 2007. What causes the great outbreak has caused widespread concern. In this study, we monitor the green tide in the SYS in 2021 using Normalized Difference Vegetation Index and Google Earth Engine and then identify the main controlling factors from environmental change and human activity. In terms of human activity, Pyropia yezoensis ( P. yezoensis ) cultivation in Northern Jiangsu shoal of China has an impact on the scale of green tide. Compared with the same period in previous years, the early recycling of P. yezoensis cultivation rafts in 2021 provided more floating seed for green tide. The human activity intensity index in coastal cities in Jiangsu and Shandong provinces of China has been increasing for the past nine years, leading to large amounts of nutrients being released into seawater, providing green tide with the nutrients needed for growth. From the perspective of environmental changes, the sea surface temperature was higher in June and July in the SYS, which was favorable for green tide growth. The abundant solar radiation in May and July is conducive to photosynthesis of Ulva prolifera. The lower photosynthetically active radiation in August is conducive to reduce the effect of photoinhibition and promote algal growth. These findings are useful for further understanding the rules of green tide outbreaks and controlling green tide disasters.